Images of Chopin in, and through, Japanese Video Games - Summers, Tim (Chopin Review, 2023)
This article examines the use of Chopin’s music in video games created by Japanese developers. While, as William Gibbons and others have documented, classical music has been used throughout the history of video games, a surprising number of Japanese games have used Chopin’s music. Sometimes this music is presented as a straightforward performance of a piece by Chopin, while others remix, vary or interpolate Chopin’s musical materials in new compositions. Chopin’s music here stages many of the tensions and possibilities found in the video game medium. In that sense, it ‘thematises’ video games. The article focuses on three aspects of Chopin in games. The first is sentimentalism (both in association with death, the supernatural and the morbid, and in association with sexual romance and romanticism more broadly). Secondly, Chopin’s music is associated with virtuosity, intertwining emotion and physicality. Finally, Chopin’s music is used as an agent for postmodern juxtaposition, in the process problematising a divide between art and mass culture. These three trends are interlinked and draw upon longstanding historical images and connotative values in relation to Chopin. The discussion builds on antecedent research concerning Chopin’s reception by Lawrence Kramer, Jim Samson, Charles Rosen and Stephen Downes, critical perspectives on games and/as musical interfaces by David Sudnow and Roger Moseley, and discussions of classical music in popular culture by Andreas Huyssen and Mina Yang. Key case studies include Space Adventure Cobra, Clock Tower 3, Eternal Sonata, Gran Turismo, Pop’n Music, Catherine and a selection of visual novels. Chopin’s music in Japanese games serves as a way to understand the meanings of that music in a modern pop-culture context. Besides that, however, such a study uncovers how the issues central to the discourse of Chopin are manifest and (re)configured in a medium and context of production very far removed from the music’s origins.